Molecular-level doped sugar-based multifunctional carbon fiber and preparation method thereof

Through wet spinning technology and pre-carbonization and carbonization treatment, multifunctional molecules are directly incorporated in the preparation stage of carbon fiber raw silk, solving the limitations and resource dependence of traditional carbon fibers, achieving efficient and green multifunctional carbon fiber synthesis, and improving the comprehensive performance of the material.

CN119843390AActive Publication Date: 2025-04-18HARBIN INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510082047.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-18
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

Traditional carbon fibers have limitations in terms of multifunctionalization, and it is difficult to directly introduce multifunctional phases in the preparation stage of the raw silk. They need to pass the secondary functionalization process in the later stage. The preparation process is complex and the energy consumption is high. They rely on non-renewable fossil resources to affect the environment and resource utilization.

Method used

By using water-soluble sugars, gel monomers and spinning additives as the main raw materials, coagulation baths and water bath solutions are prepared, carbon fiber raw silk containing multifunctional molecules is prepared by wet spinning technology, and the efficient synthesis of molecular-level doped multifunctional carbon fibers is achieved through pre-carbonization and carbonization treatment.

Benefits of technology

It realizes the direct incorporation of functional molecules in the raw silk preparation stage, significantly simplifies the process, reduces energy consumption, does not rely on non-renewable fossil resources, has the advantages of green and environmental protection, and is easy to operate, which improves the comprehensive performance of carbon fiber, including high temperature resistance, oxidation resistance, corrosion resistance, high strength, high electrical conductivity, high thermal conductivity and high specific surface area.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843390A_ABST
    Figure CN119843390A_ABST
Patent Text Reader

Abstract

The invention discloses a molecular-level doped sugar-based multifunctional carbon fiber and a preparation method thereof, and belongs to the technical field of carbon fiber preparation. The preparation method comprises the following steps: taking water-soluble saccharides, a gel monomer and a spinning aid as main raw materials, preparing a coagulating bath by using an ionic gel aid which can help fiber coagulation and can be doped with functional molecules, and carrying out wet spinning and drying to prepare the carbon fiber precursor containing the multifunctional molecules in situ. And performing pre-carbonization and carbonization treatment to realize efficient synthesis of the molecular-grade doped multifunctional carbon fiber. The introduction of the multifunctional molecules significantly improves the comprehensive properties of the carbon fiber, including high temperature resistance, oxidation resistance, corrosion resistance, high strength, high conductivity, high thermal conductivity and high specific surface area. Due to high conductivity, high specific surface area and oxidation resistance, under the support of in-situ introduction of a high pseudocapacitance substance, a strong material basis is provided for wide application of the flexible fibrous supercapacitor. The technical breakthrough is helpful for realizing an efficient and durable energy storage solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon fiber preparation, and specifically relates to a molecular-level doped sugar-based multifunctional carbon fiber and a preparation method thereof. Background Art

[0002] Traditional carbon fiber has excellent properties such as high strength, high modulus, light weight, high temperature resistance and corrosion resistance. It is widely used in aerospace, automobile manufacturing, wind turbine blades, sports equipment and building reinforcement, and can significantly improve the structural performance and durability of the material.

[0003] However, traditional carbon fibers have significant limitations in terms of multifunctionality. It is difficult to directly introduce multifunctional phases in the precursor preparation stage. This can usually only be achieved by performing secondary functionalization treatment on the finished carbon fibers. This later modification process not only relies on toxic and hazardous substances, increasing the environmental burden, but also makes the process more complicated. In addition, the preparation process of traditional polyacrylonitrile (PAN)-based carbon fibers is complex and energy-intensive, requiring multiple steps of high-temperature carbonization, which limits production and costs. The emission of harmful gases during the preparation process and the difficulty of recycling also have an adverse impact on the environment. Moreover, the main raw materials of carbon fibers rely on non-renewable fossil resources, such as PAN and asphalt, which consume a lot of resources. The above problems limit the application potential of carbon fibers in multifunctional composite materials such as electrical conductivity, thermal conductivity, and energy storage, and new methods are urgently needed to promote their multifunctionality and sustainable development. Summary of the invention

[0004] The purpose of the present invention is to provide a molecular-level doped sugar-based multifunctional carbon fiber and a preparation method thereof. By using water-soluble sugars, gel monomers and spinning aids as the main raw materials, using an ionic gel aid that can not only help the fiber coagulation but also incorporate functional molecules to prepare a coagulation bath, wet spinning and drying are performed to prepare carbon fiber precursors containing multifunctional molecules in situ, and then pre-carbonization and carbonization treatments are performed to achieve efficient synthesis of molecular-level doped multifunctional carbon fibers. Compared with traditional carbon fibers that need to be functionalized and modified in the later stage, the present invention can directly incorporate functional molecules in the precursor preparation stage, so that the functional molecules are evenly distributed, significantly simplifying the process, reducing energy consumption, not relying on non-renewable fossil resources, and having the advantages of being green, environmentally friendly, and easy to operate.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a method for preparing molecular-level doped sugar-based multifunctional carbon fibers, comprising the following steps:

[0007] Dissolving gel monomer, water-soluble sugar and cross-linking agent in water to obtain solution A; adding spinning aid, initiator and catalyst to the solution A to prepare spinning solution;

[0008] Prepare a solution identical to the solution A, add an ionic gelling agent, and use it as a coagulation bath;

[0009] Using a solution in which the gel monomer, the cross-linking agent and the spinning aid are omitted from the spinning solution as the water bath solution;

[0010] Obtaining multifunctional carbon fiber precursor by wet spinning using the spinning solution, the coagulation bath and the water bath solution;

[0011] Pre-carbonizing the multifunctional carbon fiber precursor to obtain pre-carbonized multifunctional fibers; and then carbonizing the pre-carbonized multifunctional fibers to obtain the molecular-level doped sugar-based multifunctional carbon fibers;

[0012] The ion gelling aid includes lanthanum chloride, cerium nitrate, yttrium nitrate, copper formate tetrahydrate, cobalt nitrate hexahydrate, iron nitrate nonahydrate, nickel nitrate hexahydrate, zirconium chloride, iron chloride, zirconium oxychloride, hafnium oxychloride, zirconium sulfate, titanium sulfate, titanium nitrate or zirconium acetate.

[0013] The present invention uses water-soluble sugars, gel monomers and spinning aids as main raw materials, and functionalized molecules are added with specific ionic gel aids. Carbon fiber precursors containing multifunctional molecules are prepared in situ by wet spinning and drying. The coagulation bath and water bath solutions prepared in the wet spinning process can be recycled for many times. The present invention incorporates multifunctional molecules in the precursor preparation stage; then removes volatiles and moisture by pre-carbonization, promotes caramelization reaction, reduces internal stress, avoids cracking and breaking, completes stabilization treatment, ensures fiber uniformity and strength; and finally obtains molecular-level doped multifunctional carbon fibers by carbonization.

[0014] Optionally, the gel monomer includes one or more of acrylamide, acrylic acid, methacrylic acid, polyethylene glycol diacrylate and N-isopropylacrylamide.

[0015] Optionally, the water-soluble sugar includes one or more of glucose, fructose, galactose, maltose, sucrose, lactose and oligofructose.

[0016] Optionally, the crosslinking agent includes one or more of N,N'-methylenebisacrylamide, ethylene glycol diacrylate, ethylene glycol dimethacrylate, diacrylamide ethylenediamine, polyethylene glycol diacrylate, trimethylolpropane triacrylate, divinyl urea, N,N'-ethylenebisacrylamide and N,N'-bis(acryloyloxyethyl)urea.

[0017] Preferably, the mass ratio of the gel monomer, the water-soluble sugar, the cross-linking agent and water in the solution A is 1-20:10-60:0.05-2:100.

[0018] Optionally, the spinning aid includes one or more of sodium alginate, sodium polyacrylate and sodium carboxymethyl cellulose.

[0019] Optionally, the initiator includes one or more of ammonium persulfate, azobisisobutyronitrile, potassium persulfate and hydrogen peroxide.

[0020] Optionally, the catalyst includes one or more of triethanolamine, sodium bisulfite and tetramethylethylenediamine.

[0021] Preferably, in the spinning solution, the spinning aid, initiator and catalyst are added in the form of aqueous solution, wherein the concentration of the spinning aid aqueous solution is 1-10wt.%, the concentration of the initiator aqueous solution is 0.5-20wt.%, and the concentration of the catalyst aqueous solution is 0.5-20wt.%.

[0022] Preferably, in the spinning solution, the mass ratio of the spinning aid to the water in the solution A is 0.5 to 5:100.

[0023] In the spinning solution, the amount of initiator and catalyst added is determined by the amount of gel monomer used, and can be added according to the conventional amount in the art.

[0024] Preferably, the ionic gelling agent accounts for 1-20% of the mass of the coagulation bath.

[0025] Preferably, during the wet spinning process, the temperature of the water bath solution is 25-90°C.

[0026] Preferably, in the wet spinning process, the process parameters are: spinning needle inner hole diameter 30-200 μm, spinning speed 50-2000 μL / min, drawing machine speed 1-20 m / min, drying temperature 50-300° C., and drying time 1-30 min.

[0027] Preferably, the pre-carbonization is performed by gradient heating, with the maximum temperature not exceeding 350°C.

[0028] More specific operating steps are: gradually heating the multifunctional carbon fiber precursor in a continuous pre-carbonization furnace, and evenly pulling it through each temperature zone to achieve stable pre-carbonization and obtain pre-carbonized fibers with uniform quality; the wire feeding speed is preferably 0.02-1 m / min to ensure that the fiber gradually adapts to the heating process to avoid damage to the internal structure, and the precursor has sufficient residence time in each temperature zone to react and form an ideal micro-nano structure.

[0029] Preferably, the carbonization is carried out under anaerobic conditions, with the temperature being directly or gradually increased to 800-3000° C., with a heating rate of 1-20° C. / min, and the holding time of each gradient being 0.5-6 h.

[0030] The second technical solution of the present invention is to provide a green, low-cost, sugar-based multifunctional carbon fiber prepared according to the above-mentioned method for preparing the green, low-cost, sugar-based multifunctional carbon fiber.

[0031] The third technical solution of the present invention is to provide a graphite fiber obtained by graphitizing the pre-carbonized multifunctional fiber or the molecular-level doped sugar-based multifunctional carbon fiber prepared according to the above preparation method.

[0032] Preferably, the graphitization temperature is 2000-3000° C., the heating rate is 0.5-20° C. / min, and the holding time is 0.5-6 h.

[0033] The beneficial technical effects of the present invention are as follows:

[0034] The present invention aims at the problems of long cycle, complex process, high energy consumption, high pollution and strong dependence on non-renewable fossil resources in the traditional carbon fiber preparation process, and innovatively proposes a method for preparing carbon fiber by directly incorporating multifunctional molecules in the precursor preparation stage. The method uses water-soluble sugars, gel monomers and spinning aids as raw materials, adopts wet spinning to prepare precursors containing multifunctional molecules, and through pre-carbonization and carbonization steps, realizes the efficient synthesis of multifunctional carbon fibers doped at the molecular level. The introduction of multifunctional molecules significantly improves the comprehensive properties of carbon fibers, including high temperature resistance, oxidation resistance, corrosion resistance, high strength, high conductivity, high thermal conductivity and high specific surface area. These characteristics not only make carbon fibers show broad application prospects in aerospace, automotive industry, electronic equipment, energy field, construction engineering, medical equipment and environmental protection, but also because of its high conductivity, high specific surface area and antioxidant properties, with the support of in-situ introduction of high pseudocapacitive substances, it provides a strong material basis for the wide application of flexible fiber-shaped supercapacitors. This technological breakthrough will help to achieve efficient and durable energy storage solutions. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a continuous collection production line for wet spinning in an embodiment of the present invention.

[0036] Figure 2 This is a picture of the continuous pre-carbonization furnace used in the embodiments of the present invention.

[0037] Figure 3 It is a device for carbonization or graphitization in the embodiment of the present invention.

[0038] Figure 4 This is the temperature zone setting diagram of the continuous pre-carbonization furnace in Example 1.

[0039] Figure 5 This is a picture of the nano-copper reinforced porous carbon fiber prepared in Example 1.

[0040] Figure 6The SEM images of the nano-copper reinforced porous carbon fibers prepared in Example 1, wherein (a) is a cross-sectional morphology image and (b) is a surface morphology image. DETAILED DESCRIPTION

[0041] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0042] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0043] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0045] The wet spinning continuous collection production line in the embodiment of the present invention is shown in Figure 1 .

[0046] The picture of the continuous pre-carbonization furnace used in the embodiment of the present invention is shown in Figure 2 .

[0047] The equipment for carbonization or graphitization in the embodiment of the present invention is shown in Figure 3 .

[0048] Example 1

[0049] (1) Preparation of spinning solution: First, 42 g of acrylamide, 140 g of maltose and 2.3 g of polyethylene glycol diacrylate were mixed and dissolved in 385 mL of deionized water, and stirred to form a uniform transparent solution. Then, 175 mL of a 6% sodium alginate aqueous solution, 14 mL of a 10% hydrogen peroxide aqueous solution, and 14 mL of a 10% sodium bisulfite solution were added, and ultrasonic and stirred to form a uniform solution. The bubbles in the spinning solution were removed by a debubbler to obtain a spinning solution for standby use.

[0050] (2) Preparation of coagulation bath: 1800 g of acrylamide, 6000 g of maltose, 150 g of ethylene glycol diacrylate, and 1800 g of copper formate tetrahydrate are mixed and dissolved in 16500 mL of deionized water, and stirred in a coagulation bath to form a uniform transparent solution. During the spinning operation, the circulation pump of the coagulation bath is turned on to circulate the coagulation bath in a directional manner in the coagulation bath. In addition, the coagulation bath can be recycled for multiple times after preparation.

[0051] (3) Prepare a water bath solution: 6000 g of maltose, 600 mL of a 10% by mass hydrogen peroxide aqueous solution, and 600 mL of a 10% by mass sodium bisulfite aqueous solution are mixed and dissolved in 16500 mL of deionized water, and stirred in a constant temperature water bath to form a uniform transparent solution. During the spinning operation, the heating device of the constant temperature water bath is turned on to stabilize the temperature of the water bath at 60° C. In addition, the prepared water bath solution can be recycled for multiple times.

[0052] (4) Preparation of carbon fiber precursor: Use a syringe to absorb the prepared spinning solution and connect the spinning needle. The inner diameter of the spinning needle is 80μm. Then use a high-precision injection pump to inject the spinning solution into the coagulation bath through the spinning needle at a speed of 600μL / min to generate gel fiber. After the gel fiber is pulled by a drawing machine, it passes through a 60℃ constant temperature water washing tank, the drawing machine speed is 9m / min, and it enters a 140℃ blast dryer for drying. Finally, it is collected into bundles by a collection roller to obtain carbon fiber precursor.

[0053] (5) Pre-carbonization: The carbon fiber precursor is passed through a continuous pre-carbonization furnace at a speed of 0.2m / min through a wire unwinding machine and a traction machine. The precursor is pulled through each temperature zone in a uniform manner to achieve stable pre-carbonization and obtain pre-carbonized fibers of uniform quality. The pre-carbonization production line adopts a 5-section furnace design, each furnace section has 5 temperature zones, a total of 25 temperature zones, gradually increasing from 25°C to 220°C. The temperature zones are distributed from low temperature, medium temperature to high temperature, gradually removing volatiles and moisture, promoting caramelization reaction, and completing the final stabilization treatment to ensure fiber uniformity and strength. See the temperature zone setting of the continuous pre-carbonization furnace for details. Figure 4 .

[0054] (6) Carbonization: The pre-carbonized fibers were carbonized in a carbonization furnace. Under vacuum conditions, the temperature was raised to 800°C at a heating rate of 4°C / min, kept at that temperature for 2 h, and then cooled to room temperature to obtain nano-copper reinforced porous carbon fibers.

[0055] The picture of the nano-copper reinforced porous carbon fiber prepared in Example 1 is shown in Figure 5 .

[0056] The SEM image of the nano-copper reinforced porous carbon fiber prepared in Example 1 is shown in Figure 6, where (a) is a cross-sectional morphology diagram and (b) is a surface morphology diagram. The introduction of nano-copper significantly improves the electrical conductivity of porous carbon fibers, up to 3284S / m, thanks to the excellent electrical conductivity of nano-copper and its uniform distribution in the carbon fiber matrix, thereby improving the electron transfer efficiency. At the same time, the presence of the porous structure not only greatly increases the specific surface area of ​​the carbon fiber, but also provides more adsorption and diffusion paths for electrolyte ions, further enhancing the electrochemical activity. The synergistic effect of this conductivity and porous structure provides a strong material foundation for the widespread application of flexible fibrous supercapacitors, helping them achieve breakthroughs in high energy density and high power density in the field of energy storage.

[0057] from Figure 6 It can be seen that the cross-sectional morphology of the nano-copper reinforced porous carbon fiber shows a clear porous structure. These pores are evenly distributed inside the carbon fiber, which significantly increases the specific surface area. Its surface morphology shows that there are a large number of high-contrast white bright spots on the surface. These bright spots are evenly distributed nano-copper particles, and the low-contrast dark gray area is the carbon fiber matrix. The introduction of nano-copper particles effectively enhances the electrical conductivity of carbon fiber. Its high conductivity significantly improves the electron transmission efficiency. At the same time, the porous structure provides a larger contact area and transmission path for electrolyte ions, forming an efficient ion channel and electronic network. This structural feature enables nano-copper reinforced porous carbon fiber to exhibit excellent energy storage performance in the field of flexible fibrous supercapacitors, laying a solid material foundation for achieving high energy density and high power density.

[0058] Example 2

[0059] (1) Preparation of spinning solution: First, 42 g of acrylic acid, 140 g of glucose and 2.3 g of ethylene glycol diacrylate were mixed and dissolved in 385 mL of deionized water, and stirred to form a uniform transparent solution. Then, 175 mL of a 4% sodium alginate aqueous solution, 14 mL of a 10% ammonium persulfate aqueous solution, and 14 mL of a 10% tetramethylethylenediamine aqueous solution were added, and ultrasonic and stirred to form a uniform solution. The bubbles in the spinning solution were removed by a debubbler to obtain a spinning solution for standby use.

[0060] (2) Preparation of coagulation bath: 1800 g of acrylic acid, 6000 g of glucose, 150 g of ethylene glycol diacrylate, and 1800 g of zirconium oxychloride are mixed and dissolved in 16500 mL of deionized water, and stirred in a coagulation bath to form a uniform transparent solution. During the spinning operation, the circulation pump of the coagulation bath is turned on to circulate the coagulation bath in a directional manner in the coagulation bath. In addition, the coagulation bath can be recycled for multiple times after preparation.

[0061] (3) Preparation of water bath solution: 6000 g of glucose, 600 mL of 10% by mass ammonium persulfate aqueous solution, and 600 mL of 10% by mass tetramethylethylenediamine aqueous solution are mixed and dissolved in 16500 mL of deionized water, and stirred in a constant temperature water bath to form a uniform transparent solution. During the spinning operation, the heating device of the constant temperature water bath is turned on to stabilize the temperature of the water bath at 70° C. In addition, the water bath solution can be recycled many times after preparation.

[0062] (4) Preparation of carbon fiber precursor: Use a syringe to absorb the prepared spinning solution and connect the spinning needle. The inner diameter of the spinning needle is 80μm. Then use a high-precision injection pump to inject the spinning solution into the coagulation bath through the spinning needle at a speed of 500μL / min to generate gel precursor. After the gel precursor is pulled by a drawing machine, it passes through a 70℃ constant temperature water washing tank, the drawing machine speed is 8m / min, and it enters a 120℃ blast dryer for drying. Finally, it is collected into bundles by a collection roller to obtain carbon fiber precursor.

[0063] (5) Pre-carbonization: The carbon fiber precursor is passed through a continuous pre-carbonization furnace at a speed of 0.05 m / min through a wire unwinding machine and a traction machine. The precursor is pulled through each temperature zone in a uniform manner to achieve stable pre-carbonization and obtain pre-carbonized fibers of uniform quality. The pre-carbonization production line adopts a 5-section furnace design, each furnace section has 5 temperature zones, a total of 25 temperature zones, gradually increasing from 25°C to 220°C. The temperature zones are distributed from low temperature, medium temperature to high temperature, gradually removing volatiles and moisture, promoting caramelization reaction, and completing the final stabilization treatment to ensure fiber uniformity and strength. See the temperature zone setting of the continuous pre-carbonization furnace for details. Figure 4 .

[0064] (6) Carbonization: The pre-carbonized fibers were carbonized in a carbonization furnace. Under vacuum conditions, the temperatures were raised to 360°C, 920°C, 1050°C, and 1400°C at a heating rate of 4°C / min, and each temperature was kept for 2 h. The furnace was then cooled to room temperature to obtain nano-zirconia reinforced carbon fibers.

[0065] The oxidation starting temperature of the nano-zirconia reinforced carbon fiber prepared in Example 2 is as high as 748°C.

[0066] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing green and low-cost sugar-based multifunctional carbon fiber, characterized in that: The following steps are involved: Dissolving gel monomer, water-soluble sugar and cross-linking agent in water to obtain solution A; Adding a spinning aid, an initiator and a catalyst into the solution A to prepare a spinning solution; Prepare a solution identical to the solution A, add an ionic gelling agent, and use it as a coagulation bath; Using a solution in which the gel monomer, the cross-linking agent and the spinning aid are omitted from the spinning solution as the water bath solution; Obtaining multifunctional carbon fiber precursor by wet spinning using the spinning solution, the coagulation bath and the water bath solution; Pre-carbonizing the multifunctional carbon fiber precursor to obtain pre-carbonized multifunctional fibers; and then carbonizing the pre-carbonized multifunctional fibers to obtain the green, low-cost sugar-based multifunctional carbon fibers; The ion gelling aid includes lanthanum chloride, cerium nitrate, yttrium nitrate, copper formate tetrahydrate, cobalt nitrate hexahydrate, iron nitrate nonahydrate, nickel nitrate hexahydrate, zirconium chloride, iron chloride, zirconium oxychloride, hafnium oxychloride, zirconium sulfate, titanium sulfate, titanium nitrate or zirconium acetate.

2. The method for preparing green, low-cost sugar-based multifunctional carbon fibers according to claim 1, characterized in that: The mass ratio of the gel monomer, the water-soluble sugar, the cross-linking agent and water in the solution A is 1-20:10-60:0.05-2:

100.

3. The method for preparing green, low-cost sugar-based multifunctional carbon fibers according to claim 1, characterized in that: In the spinning solution, the spinning aid, initiator and catalyst are added in the form of aqueous solution, wherein the concentration of the spinning aid aqueous solution is 1-10wt.%, the concentration of the initiator aqueous solution is 0.5-20wt.%, and the concentration of the catalyst aqueous solution is 0.5-20wt.%.

4. The method for preparing green and low-cost sugar-based multifunctional carbon fiber according to claim 1, characterized in that: In the spinning solution, the mass ratio of the spinning aid to the water in the solution A is 0.5 to 5:

100.

5. The method for preparing green and low-cost sugar-based multifunctional carbon fiber according to claim 1, characterized in that: The ionic gelling agent accounts for 1 to 20% of the mass of the coagulation bath.

6. The method for preparing green and low-cost sugar-based multifunctional carbon fiber according to claim 1, characterized in that: In the wet spinning process, the process parameters are: the inner hole diameter of the spinning needle is 30-200 μm, the spinning speed is 50-2000 μL / min, the drawing machine speed is 1-20 m / min, the drying temperature is 50-300° C., and the drying time is 1-30 min.

7. The method for preparing green and low-cost sugar-based multifunctional carbon fiber according to claim 1, characterized in that: The pre-carbonization is performed by gradient heating, and the maximum temperature does not exceed 350°C.

8. The method for preparing green and low-cost sugar-based multifunctional carbon fiber according to claim 1, characterized in that: The carbonization is carried out under anaerobic conditions, and the temperature is directly or gradually increased to 800-3000° C., the heating rate is 1-20° C. / min, and the insulation time of each gradient is 0.5-6h.

9. A green, low-cost sugar-based multifunctional carbon fiber prepared according to the method for preparing green, low-cost sugar-based multifunctional carbon fiber according to any one of claims 1 to 8.

10. A graphite fiber, characterized in that: The method is obtained by graphitizing the pre-carbonized multifunctional fiber or the molecular-level doped sugar-based multifunctional carbon fiber prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Graphene composite fiber and preparation method thereof

    CN116876109A

  • Ablation-resistant modified glycosyl carbon fiber composite material and preparation method thereof

    CN119307061A

  • Carbon fiber precursor, method of producing carbon fiber precursor, method of producing stabilized fiber, and method of producing carbon fiber

    US20230129865A1